Electronic Structure Changes of an Aromatic Amine Photoacid along the Förster Cycle. Issue 27 (27th April 2022) - Eckert, Sebastian; Winghart, Marc‐Oliver; Kleine, Carlo; Banerjee, Ambar; Ekimova, Maria; Ludwig, Jan; Harich, Jessica; Fondell, Mattis; Mitzner, Rolf; Pines, Ehud; Huse, Nils; Wernet, Philippe; et al.
Abstract: Photoacids show a strong increase in acidity in the first electronic excited state, enabling real‐time studies of proton transfer in acid‐base reactions, proton transport in energy storage devices and biomolecular sensor protein systems. Several explanations have been proposed for what determines photoacidity, ranging from variations in solvation free energy to changes in electronic structure occurring along the four stages of the Förster cycle. Here we use picosecond nitrogen K‐edge spectroscopy to monitor the electronic structure changes of the proton donating group in a protonated aromatic amine photoacid in solution upon photoexcitation and subsequent proton transfer dynamics. Probing core‐to‐valence transitions locally at the amine functional group and with orbital specificity, we clearly reveal pronounced electronic structure, dipole moment and energetic changes on the conjugate photobase side. This result paves the way for a detailed electronic structural characterization of the photoacidity phenomenon. Abstract : Electronic structural changes along the Förster cycle of an aromatic amine photoacid are monitored with time‐resolved nitrogen K‐edge spectroscopy, providing key insight into the factors responsible for the photoacidity properties.